Modulation of Conjunctival Goblet Cell Function by Inflammatory Cytokines - Contreras-Ruiz, L.; Ghosh-Mitra, A.; Shatos, M. A.; Dartt, D. A.; Masli, S. (Mediators of Inflammation, 2013)
Ocular surface inflammation associated with Sjögren’s syndrome is characterized by a loss of secretory function and alteration in numbers of mucin secreting goblet cells. Such changes are a prominent feature of ocular surface inflammatory diseases and are attributed to inflammation; however, the exact effect of the inflammatory cytokines on conjunctival goblet cell function remains largely unknown. In this study, we developed a primary culture of mouse goblet cells from conjunctival tissue and evaluated the effects on their function by inflammatory cytokines detected in the conjunctiva of mouse model of Sjögren’s syndrome (Thrombospondin-1 deficient mice). We found that apoptosis of goblet cells was primarily induced by TNF-α and IFN-γ. These two cytokines also inhibited mucin secretion by goblet cells in response to cholinergic stimulation, whereas IL-6 enhanced such secretion. No changes in secretory response were detected in the presence of IL-13 or IL-17. Goblet cells proliferated to varying degrees in response to all the tested cytokines with the greatest response to IL-13 followed by IL-6. Our results therefore reveal that inflammatory cytokines expressed in the conjunctiva during an ocular surface disease directly disrupt conjunctival goblet cell functions, compromising the protective function of tears, thereby contributing to ocular surface damage.